Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{\left(3-x\right)^{10x}}{\left(3-x\right)^{20}}=1\Leftrightarrow\left(3-x\right)^{10x-20}=\left(3-x\right)^{10\left(x-2\right)}=1\\ \)
\(\orbr{\begin{cases}x-2=0=>x=2\\3-x=+-1\orbr{\begin{cases}x=2\\x=4\end{cases}}\end{cases}}\)\(\orbr{\begin{cases}x-2=0\Rightarrow x=2\\3-x=!1!\end{cases}}\)\(\orbr{\begin{cases}x=2\\x=4\end{cases}}\)
c) [3 - x]^10x : [3 - x]^20 = 1
Ta thấy [3 - x]^10x : [3 - x]^20 = 1 => [3 - x]^10x = [3 - x]^20 vì a : a = 1
[3 - x](1) = [3 - x](2) nên ta không xét, vậy ta chỉ xét hai số mũ 10x và 20
10x = 20 => x = 20 : 10 => x = 2
Vậy x = 2
\(\left(2x-3\right)^{10x}=\left(3-2x\right)^{100}\)
\(\Leftrightarrow\left(2x-3\right)^{10x}=\left(2x-3\right)^{100}\)
\(\Leftrightarrow10x=100\Leftrightarrow x=100:10=10\)